2023
DOI: 10.1097/j.jcrs.0000000000001112
|View full text |Cite
|
Sign up to set email alerts
|

Female authorship trends and the effect of COVID-19 on cataract and refractive surgery literature

Abstract: To evaluate whether gender barriers persist specifically in the cataract and refractive surgery (CRS) literature. In addition, no literature exists investigating the long-term effect of COVID-19 on female authorship in ophthalmology past 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a few studies of academic ophthalmologists, men were found to have significantly higher average h-indices than women. 13,32,40 Findings were similar in the subspecialties of cornea, 23 oculoplastics, 25 paediatrics, 29 and retina. 33,36 Whereas these differences in productivity are seen in studies focused on global or US-based ophthalmologists, the trends differ among subgroups of ophthalmologists.…”
Section: Markers Of Productivitymentioning
confidence: 74%
See 1 more Smart Citation
“…In a few studies of academic ophthalmologists, men were found to have significantly higher average h-indices than women. 13,32,40 Findings were similar in the subspecialties of cornea, 23 oculoplastics, 25 paediatrics, 29 and retina. 33,36 Whereas these differences in productivity are seen in studies focused on global or US-based ophthalmologists, the trends differ among subgroups of ophthalmologists.…”
Section: Markers Of Productivitymentioning
confidence: 74%
“…30,31 One study of the cornea subspecialty showed an increase in female last authors but not first. 22 This was not the case, however, for glaucoma 24 or refractive surgery, 32 although neither study was able to compare their growth data to that of women practicing in the respective subspecialty.…”
Section: Proportion Of Female Authors Over Timementioning
confidence: 99%